Overview of oil spills worldwide and impacts on marine megafauna - Silva, Flávio José de Lima; Attademo, Fernanda Loffler Niemeyer; Gavilan, Simone Almeida; Rossi, Silmara; Farias, Daniel Solon Dias de; Bomfim, Aline da Costa; Oliveira, Rysónely Maclay de; Fragoso, Ana Bernadete Lima; Corrêa, Gabriela Colombini; Santoro, Giovanna Almeida; Ambrósio, Gustavo Magno Lima; Lima, Mariana Almeida; et al. (Brazilian Journal of Case Reports, 2024)
Oil spills have a significant impact on the environment, posing threats to various marine species. This review aims to gather information on various oil spills that have occurred worldwide and discuss their impact on marine megafauna (marine mammals, sea turtles, and seabirds), in order to provide useful insights that can be applied in decision-making during rescue and rehabilitation efforts. The publications were obtained from oil spill searches in databases such as Elsevier-Scopus, Scielo, JStor, and Google Scholar. Oil spills can cause lethal damage to marine biodiversity, affecting individuals of different ages and species. Although the acute effects of oil contamination on wildlife are evident, it is challenging to treat and recover from. Hydrocarbons can persist in the environment for a long time, leading to prolonged exposure of animals to the contaminants. In conclusion, this research demonstrates that the effects of oil spills on marine megafauna may not be observed in the short term, such as contamination through the bioaccumulation of compounds in the food chain. It is necessary to conduct systematic studies on local fauna at all developmental stages of oil activities, including seismic research, exploration, and oil distribution to address the impact of oil spills on marine megafauna.